Effectiveness of synbiotics as laxative agent for constipation in children - Hannah Hannah; M. Juffrie; S. Yati Soenarto (Indonesian Pediatric Society Publishing House, 2016)
Background Constipation in children can cause serious problems. Laxative is needed for the management of constipation. Oral laxative has been used frequently, even though a safe oral laxative agents for children is limited. Prebiotic and probiotic have already been proven to have laxative effect in constipation in children and adults. The effectiveness of these agents as a laxative has not been proven yet. Objective To evaluate the effectiveness of laxative synbiotic in constipation in children compared to that of fiber foods. Methods A randomized double blind controlled trial was conducted on children aged 6 months-14 years old who suffered from functional constipation at Dr. Sardjito Hospital, Dr. Soeradji Tirtonegoro Hospital, and Wates District Hospital from April2007 -October 2007. Randomization was performed by computer. The outcome of recovery rate, onset therapy and side effects were evaluated after seven days of intervention. Results Forty-three children were included in this study, but only 41 could be analyzed. Subject characteristics in both groups were comparable except for maternal educational level. The main outcome (recovery rate) was assessed by intention to treat principle. Compared with fiber foods, synbiotic increased the recovery rate with RR 2.14 (95%CI 1.14; 4.02) and NNT 2.9 (95%CI 2; 15), whereas its therapeutic onset was 15 hours faster than that of fiber foods. No important side effects were found in both groups. Conclusions Synbiotic is safe and effective in increasing the recovery rate of functional constipation with faster therapeutic onset than that of fiber foods.